Mapeamento geológico - estrutural do astroblema de cerro do Jarau - RS Brasil - Sánchez, Joana Paula [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Cerro do Jarau structure is located in the Rio Grande do Sul state, nearby the Quaraí city, in the limit with Uruguai. The origin of its circular feature has been a source of question for decades. In this work the deepening of the geological knowledge of this strucuture was done and generated a new understanding of the local stratigraphy and the rock structuring that compose this astroblem. The structure was interpreted as a structural dome formed by tectonic after the Botucatu Formation sandstone deposition and before the basalt flows of the Serra Geral Formation, authors point out that the circular structure is highlighted in the region, with the occurence of the Botucatu Formation sandstones uplifted in the center and Serra Geral Formation basalts on the edge. This Thesis present new geological mapping data that demonstrate that the Cerro do Jarau region sandstones are structured in a basin shape, not a dome, and the sandstone package that occurs in the central portion is superimposed to basalts located in its surroundings. Detailed field and mapping work at 1: 10 000 scale were realized and allowed the identification of the preferred bedding plans attitudes that points the dip to the center of the structure, setting a concave shape, as a basin shape. Such interpretation was possible by the direct field observation and by the drawing of the sediment/basalt contact (V rule) which show that the sandstone package is overlapped to basalts. Petrographic analysis allowed to separate the lithological units in three main units, among them the Serra Geral Formation Unit with basalt, igneous breccias and intertrap sandstones, Homogeneous Sandstone Unit and Laminated Sandstone Unit. Analysis of scanning electron microscopy allowed the characterization of the intragranular fractures in the sandstones and characterization of the veining observed in the basalts. Geochemical analysis of the basalts allowed the comparison of the internal and...

A estrutura do Cerro do Jarau está localizada no Estado do Rio Grande do Sul, nas proximidades da cidade de Quarai, divisa com o Uruguai. A origem de sua feição circular é motivo de indagações há décadas. Neste trabalho foi realizado o aprofundamento do conhecimento geológico dessa estrutura que gerou uma nova compreensão da estratigrafia local e da estruturação das rochas que compõem esse astroblema. A estrutura era interpretada como um domo estrutural formado por tectônica após a deposição dos arenitos da Formação Botucatu e antes dos derrames basálticos da Formação Serra Geral, autores ressaltam que a estrutura circular se destaca na região, com a ocorrência de arenitos da Formação. Botucatu, soerguidos no centro, e basaltos da Formação. Serra Geral, na borda, com estratigrafia com os arenitos por baixo e o basalto por cima. Esta tese apresenta novos dados de cartografia geológica que demonstram que os arenitos da região do Cerro do Jarau encontram-se estruturados na forma de uma bacia, e não de um domo, e que o pacote de arenitos que ocorre na porção central encontra-se sobreposto aos basaltos situados em seu entorno. Foram realizados trabalhos de campo e o mapeamento de detalhe em escala 1:10.000, que permitiu a identificação das atitudes preferenciais dos planos de acamamento que evidenciam o mergulho para o centro da estrutura, configurando uma forma côncava, tipo bacia. Tal interpretação foi possível através das observações diretas no campo e pelo desenho do contato arenito/basalto (regra dos Vs) que evidenciam que o pacote de arenitos encontra-se sobreposto aos basaltos. Análises petrográficas permitiram separar as Unidades Litológicas em três unidades principais, dentre elas Unidades da Formação Serra Geral, com basaltos, brechas ígneas e arenitos intertrapa, Unidade dos Arenitos Homogêneos e Unidade dos Arenitos Laminados. Análises de microscopia eletrônica de varredura permitiram...
Keywords: Geology, Stratigraphic; Geologia estratigráfica; Mapeamento geologico; Crateras de impacto; Geoquimica; Montanhas; Geomorfologia; Tempo geológico; Jarau, Cerro do (RS)